Research of the Passenger’s Preferences and Requirements for the Travel Companion Application - Anna Dolinayova; Jaroslav Masek; Martin Kendra; Juraj Čamaj; Delphine Grandsart; Evelien Marlier; Paola Colzani; Marika Arena; Jonathan Paragreen; Piraba Navaratnam; Martin Brennan; Tomas Paleta (Journal of Advanced Transportation)
Currently, passengers have access to a lot of information when planning their trip by public transport. They can use a lot of applications, which are not compatible with each other. Sometimes it can be even quite difficult to collect all relevant information. The creation of one application (Travel Companion), which contains all relevant data needed for optimal planning of a trip can make travelling by public transport more attractive. This paper identifies and describes conditions for a large market uptake of the Travel Companion approach by the end-users: the travellers. The paper deals with research of the passenger’s preferences and requirements for the travel companion. Research consists of four steps based on analyses of interaction points, interviews, and workshops. Every step of methodology brings interesting feedback on the design and functionality of the travel companion. The paper is based on particular results of the H2020 project - 730842 Governance of the Interoperability Framework for Rail and Intermodal Mobility (GoF4R).